In vivo functional properties of juxtaglomerular neurons in the mouse olfactory bulb - Homma, Ryota; Kovalchuk, Yury; Konnerth, Arthur; Cohen, Lawrence B.; Garaschuk, Olga (Frontiers in Neural Circuits, 2013)
Juxtaglomerular neurons represent one of the largest cellular populations in the mammalian olfactory bulb yet their role for signal processing remains unclear. We used two-photon imaging and electrophysiological recordings to clarify the in vivo properties of these cells and their functional organization in the juxtaglomerular space. Juxtaglomerular neurons coded for many perceptual characteristics of the olfactory stimulus such as (i) identity of the odorant, (ii) odorant concentration, (iii) odorant onset and (iv) offset. The odor-responsive neurons clustered within a narrow area surrounding the glomerulus with the same odorant specificity, with ~80% of responding cells located ≤ 20 µm from the glomerular border. This stereotypic spatial pattern of activated cells persisted at different odorant concentrations and was found for neurons both activated and inhibited by the odorant. Our data identify a principal glomerulus with a narrow shell of juxtaglomerular neurons as a basic odor coding unit in the glomerular layer and underline the important role of intraglomerular circuitry.